2019
DOI: 10.1128/mra.01093-19
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Escherichia coli Phage Paul

Abstract: Escherichia coli is both a commensal and a pathogen in humans and other animals. Here, we describe the isolation of E. coli strain 4s bacteriophage Paul. The complete 79,429-bp genome was annotated and demonstrates similarity with phieco32viruses, as does its prolate podophage morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In more modern approaches, DNA termini are often computed based off raw short-read sequence data via the analysis of starting positive coverage [ 63 ]. With this approach, the termini of only two other group phages have been determined, SU7 and Paul phages, with noted DTRs of 53 bp (cautioned by the authors) and 193 bp, respectively [ 56 , 61 ]. Given the YF01 phage was sequenced with nanopore long-read technology, we curated reads spanning the entire YF01 genome sequence (~78,600 bp; many >Q30 due to duplex strand basecalling) and analyzed the DNA termini.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In more modern approaches, DNA termini are often computed based off raw short-read sequence data via the analysis of starting positive coverage [ 63 ]. With this approach, the termini of only two other group phages have been determined, SU7 and Paul phages, with noted DTRs of 53 bp (cautioned by the authors) and 193 bp, respectively [ 56 , 61 ]. Given the YF01 phage was sequenced with nanopore long-read technology, we curated reads spanning the entire YF01 genome sequence (~78,600 bp; many >Q30 due to duplex strand basecalling) and analyzed the DNA termini.…”
Section: Resultsmentioning
confidence: 99%
“…In the YF01 phage, the extended MCP isoform is substantially larger (892 a.a) than those seen in many other group members (~500–550 a.a) and most similar in size to that seen in the Paul phage (894 a.a.) [ 56 ]. As observed in T3 phage [ 67 ], the extended MCP isoform results in the addition of an immunoglobulin (Ig)-like domain to the C-terminus of the MCP.…”
Section: Resultsmentioning
confidence: 99%
“…TEM imaging demonstrated that phages 7-11, Lah_6, and Vp_R1 each belong to the C3 podophage morphotype. Privateer also shares similar proteins with phages in the Kuravirus genus, including Escherichia phages phiEco32 (33 similar proteins) ( Savalia et al, 2008 ), Paul (33 proteins) ( Holt et al, 2019 ) and vB_EcoP_SU10 (32 similar proteins) ( Mirzaei et al, 2014 ). The Kuravirus genus is within the Podoviridae family and consists of C3 morphotype (prolate) phages, with phiEco32 as the exemplar.…”
Section: Resultsmentioning
confidence: 99%
“…It has an elongated head, with a length of 134 nm (134 ± 6 nm) and width of 44 nm (44 ± 2 nm), and a very short non-contractile tail, which could not be measured ( Figure 1 B). Occurring in less than 1% of Podoviridae virions, this rare morphotype has been observed among phages belonging to the Kuravirus genus (previously referred to as PhiEco32viruses) and include the E. coli phages vB_EcoP_SU10, Paul, and phiEco32 [ 47 , 48 , 49 , 50 ]. At an MOI of 0.12, SU7 has a latency period of 30 min (defined as the time from the addition of phages to a significant rise in phage concentration) and a burst size of 12 PFU/cell ( Figure 2 and Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%